ANALISIS JUMLAH LEUKOSIT DAN TROMBOSIT PADA PASIEN DEMAM TIFOID DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2022 - Paska Situmorang; Thesiafuji Reza Simanullang; Rayani Bangun (Poltekkes Kemenkes Medan, 2022)
Typhoid fever is a disease caused by a systemic infection characterized by fever and abdominal pain due to the spread of Salmonella bacteria. Leukocytes are white blood cells that function to protect the body from the threat of infection, infectious diseases and attacks by foreign and harmful substances. Platelets play a role in the process of wound closure and stop bleeding. Patients with typhoid fever in Indonesia are reported to be 81.7 per 100,000 population. One of the supporting tests for typhoid fever is the examination of the number of leukocytes and platelets.This study aims to determine the frequency distribution of leukocytes and platelets in patients with typhoid fever at Santa Elisabeth Hospital Medan. The type of observational research is to observe the object or subject under study without intervening with a cross sectional approach with the population obtained from medical record data, namely all inpatients and outpatients suffering from typhoid fever at Santa Elisabeth Hospital Medan for the last 3 months starting from from January 2022 to March 2022 as many as 33 people. The sample in this study amounted to 33 people with saturated sampling technique. Data collection is obtained through media record data and the results of the examination of the number of leukocytes and platelets. The results showed that more typhoid fever respondents have normal leukocyte counts as many as 15 respondents (45.5%) and more have low platelet counts as many as 16 respondents (48.5%). Typhoid fever patients were found more in female respondents (60.6%) than male respondents (39.4%). The age category that suffered the most from typhoid fever with an age range of 1-9 years was 15 respondents (45.5%). The conclusion of this study is that there are decreased, normal, and increased numbers of leukocytes and platelets in typhoid fever patients